The Effectiveness of a Smart TV–Based Reality Approach in Improving the Understanding of Daily Prayers among Students with Intellectual Disabilities - aria Hermawan; Khotimatus Sholikhah; Muchamad Suradji (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the effectiveness of a reality-based approach integrated with Smart TV in improving students’ understanding of daily prayers among students with intellectual disabilities. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were five students with mild and moderate intellectual disabilities at SLB Putra Mandiri Lamongan. Data were collected through tests, observations, and documentation, and analyzed using descriptive quantitative and qualitative approaches, with a success indicator of at least 75% of students achieving the Minimum Mastery Criteria (MMC) of 75. the results showed a significant improvement in students’ understanding, indicated by an increase in the average score from 68.00 in the pre-cycle to 77.00 in Cycle I and 84.00 in Cycle II. The learning mastery percentage also improved from 20% to 60% and reached 80% in Cycle II. These findings highlight that the integration of a reality-based approach with Smart TV creates a more contextual and interactive learning environment suited to students with intellectual disabilities. The novelty of this study lies in the pedagogical integration of Smart TV within the reality approach in Islamic Religious Education learning.